1989
DOI: 10.3181/00379727-190-42823
|View full text |Cite
|
Sign up to set email alerts
|

Luteinizing Hormone Secretion in Hypophysial Stalk-Transected Pigs Given Progesterone and Pulsatile Gonadotropin-Releasing Hormone

Abstract: This study was conducted to determine whether progesterone inhibits luteinizing hormone (LH) secretion in female pigs by a direct action on the pituitary gland. Eight ovariectomized, hypophysial stalk-transected gilts were given 1-pg pulses of gonadotropin-releasing hormone iv every 45 min from Day 0 to 12. On Days 5-12, each of four gilts received either progesterone or oil vehicle im at 12-hr intervals. Serum progesterone concentrations in steroid-treated gilts reached 70 2 6.8 ng/ml (mean 2 SE) by Day 8 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1991
1991
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Secretion of FSH was also abolished after passive immunization against GnRH Esbenshade et al, 1986), but not after hypophysial stalk section . Progesterone (Estienne et al, 1989) and cortisol (unpublished) failed to suppress LH secretion in response to pulsatile administration of GnRH in hypophysial stalk-sectioned gilts, indicating that the well documented negative feedback action of these steroids on pulsatile LH secretion in pigs occurs at the CNS rather than at the pituitary gland.…”
Section: Gonadotrophin 'Pulse Generator'mentioning
confidence: 97%
“…Secretion of FSH was also abolished after passive immunization against GnRH Esbenshade et al, 1986), but not after hypophysial stalk section . Progesterone (Estienne et al, 1989) and cortisol (unpublished) failed to suppress LH secretion in response to pulsatile administration of GnRH in hypophysial stalk-sectioned gilts, indicating that the well documented negative feedback action of these steroids on pulsatile LH secretion in pigs occurs at the CNS rather than at the pituitary gland.…”
Section: Gonadotrophin 'Pulse Generator'mentioning
confidence: 97%
“…The P4 acts on the hypothalamus to inhibit GnRH secretion and in 4 turn decreases LH production from the anterior pituitary gland. A hypothalamic site for the negative feedback action of the P4 on LH secretion was supported by work from Estienne et al (1989) who demonstrated that P4 did not suppress the secretion of LH in response to pulsatile injections of GnRH in hypophyseal stalk-transected pigs. The inhibition of LH and FSH prevents ovarian follicles from growing to the pre-ovulatory stage and being further selected for ovulation.…”
Section: Introductionmentioning
confidence: 96%